Memoirs of Louis XIV and His Court and of the Regency $1 (BVolume 05s - Saint-Simon, Louis de Rouvroy, duc de, 1675-1755 (Salt Lake City, UT : Project Gutenberg, 2004)
"Memoirs of Louis XIV and His Court and of the Regency $1 (BVolume 05" by the Duke of Saint-Simon is a historical account composed in the early 18th century. The book delves into the life and court of King Louis XIV, covering significant events, notable figures, and the intrigues of the French nobility during his reign and the subsequent Regency period. The narrative unfolds through detailed anecdotes and reflections, highlighting the characters and political dynamics that shaped the time. The opening of this volume introduces two prominent figures: Lamoignon, the Chief President, and Ninon de l'Enclos, a celebrated courtesan. As Lamoignon's morally dubious actions lead to the execution of the wrongfully accused Fargues, it sets a tone of political corruption within the court. Meanwhile, Ninon's reputation precedes her; she embodies a blend of charm and cunning intellect, managing her romantic liaisons with an intriguing social sophistication. Both deaths, unfolded through engaging narratives, foreshadow a deeper exploration of the evolving court dynamics and military challenges facing France during this tumultuous historical period. The storyteller, seeming to navigate the corridors of power while observing these characters, hints at the intricate interplay of personal relationships and political maneuvering that defined the era. This opening provides a compelling glimpse into the complex tapestry of the French court, piquing the interest of readers in the detailed chronicles that are to follow. (This is an automatically generated summary.)s
Release date is 2004-12-03
Produced by David Widger
Keywords: France -- Court and courtiers; France -- History -- Louis XIV, 1643-1715; France -- History -- Regency, 1715-1723